Chance-constrained optimal dispatch of integrated electricity and natural gas systems considering medium and long-term electricity transactions - Wu, Gang; Xiang, Yue; Liu, Junyong; Zhang, Xin; Tang, Shuoya (IEEE, 2019)
A novel stochastic optimal dispatch model considering medium and long-term electricity transaction for a wind power integrated energy system by using chance constrained programming is proposed. The electricity contract decomposition problem is introduced into the day-ahead optimal dispatch plan formulation progress. Considering the case that decomposition results may be not executable in the dispatch plan, a coordinated optimization strategy based on Lagrange multiplier is proposed to locate the infeasible factors and eliminate the non executable electric quantity. At the same time, the uncertainties and correlation of wind power are considered in the dispatch model, and the original stochastic dispatch problem is transformed into a mixed integer second-order cone programming problem based on second-order cone relaxation and deterministic transformation of chance constraints. Case study results demonstrate the validity of the proposed method
Keywords: Chance-constrained programming; medium and long-term electricity transaction; wind power; uncertainties